EFEKTIFITAS MEDIATOR DALAM PENYELESAIAN SENGKETA PERDATA DI PENGADILAN NEGERI - Aulia Nur Jamilah (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT              Law is a set of written and unwritten rules if violated will be sanctioned. Therefore, the existence of the law will protect the rights and obligations of each legal subject peacefully, while peace itself is a harmony between the order (order) with peace, civil cases court process is a process of fact finding and information from both sides, as a judge act as a mediator or a neutral third party, will guide and assess reasonable attention to the opinions of both parties and in case of an agreement will be formalized in a decision which it confirms the legal rights and obligations of the parties          Decision peace also has the power executorial as well as court rulings and binding affirmed in Article 130 paragraph (2) HIR. Decision deed of this peace can not compared because under Article 154 Rbg / 130 HIR, deed decision peace is a supreme decision and no appeal and cassation against him. Implementation of PERMA No. 1 of 2008 on mediation procedure in this trial has yet to bring success. In an attempt to give birth to a mediator who has skills as a trial partner, is expected to Each and Every court to mediation training event for mediators. Keywords ; mediator , Perma No.1 Tahun 2008